2006
DOI: 10.1191/0267659106pf851oa
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac organ donor management

Abstract: There is a critical shortage of donor organs. According to the United Network for Organ Sharing (UNOS), 20% of organs are discarded after procurement. Many of these may be potentially salvageable. Brain death is particularly detrimental to cardiac function. The initial sympathetic storm can produce direct myocardial injury. The ensuing spinal shock reduces global oxygen delivery. There is a change to anaerobic metabolism due to global mitochondrial dysfunction. Diabetes insipidus worsens hypovolemia and thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Continued increases in pressure then may lead to transtentorial (central) herniation syndromes with distortion of the posterior fossa and brain stem displacement through the foramen magnum. 13,[17][18][19][20] The Cushing response, due to pressure or ischemia on the pons, is considered a reflex response to maintain brain perfusion in patients with elevated ICPs and is characterized by hypertension, bradycardia, and widened pulse pressure. 20 Progression of ischemia or distortion of the medulla oblongata and hypothalamus results in additional sympathetic outflow as endogenous catecholamine stores are released, causing hypertension, tachycardia, and vasoconstriction in an effort to maintain cerebral perfusion pressure.…”
Section: Pathophysiology Of Brain Injurymentioning
confidence: 99%
“…Continued increases in pressure then may lead to transtentorial (central) herniation syndromes with distortion of the posterior fossa and brain stem displacement through the foramen magnum. 13,[17][18][19][20] The Cushing response, due to pressure or ischemia on the pons, is considered a reflex response to maintain brain perfusion in patients with elevated ICPs and is characterized by hypertension, bradycardia, and widened pulse pressure. 20 Progression of ischemia or distortion of the medulla oblongata and hypothalamus results in additional sympathetic outflow as endogenous catecholamine stores are released, causing hypertension, tachycardia, and vasoconstriction in an effort to maintain cerebral perfusion pressure.…”
Section: Pathophysiology Of Brain Injurymentioning
confidence: 99%
“…The most important endocrine disturbances are a reduction in anti-diuretic hormone secretion, thyroid dysfunction, reduction in adenocorticotrophic hormone and insulin levels (Ullah et al 2006). In experimental animal models of brain death, the pituitary gland hormones vasopressin and adenocorticotrophic hormone decreased significantly after 15 and 45 minutes of brain death respectively (Bittner et al 1995).…”
Section: Pathophysiologymentioning
confidence: 99%
“…It has been defined "sick euthyroid syndrome" and has also been described in cardiopulmonary by-pass. It is postulated that proinflammatory cytokines may play a role in inhibiting the conversion of thyroxine to the active form of thyroid hormone, and instead, convert it to the non-active form, reverse-thyroid hormone (Ullah et al 2006). In an animal model of brain death, Novitzky et al showed that levels of thyroid hormones were severely depleted (Novitzky et al 1988).…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations